Pengaruh Perawatan Metode Kangguru terhadap Stress Hemodinamik pada Bayi Berat Lahir Rendah di RS Annisa Tangerang 2020 - Nurpaijah Nurpaijah; Ria Setia Sari (Jurnal Health Sains, 2021)
Conditions in Neonatology in the form of noise, lighting, smells, the use of tools and procedures that can cause stress and pain greatly contribute to morbidity. Newborns are often exposed to a number of procedures that cause pain, both diagnostic procedures, therapeutic procedures, and installation of monitoring tools. Physiological parameters. All of these actions can put stress on the baby. The impact if the baby is stressed is a change in  the baby's physiological functions, such as hypothermia, an increase in the baby's heart rate, the frequency of breath will cause repeated apnea, the presentation of hemoglobin bound by oxygen (SPO2) tends to decrease. The purpose of this study was to determine the effect of Kangaroo Treatment Method on Physiological Stress in Low Birth Weight Infants at Rs Annisa Tangerang 2020. The research method used in this study was a quasi experimental design: one group pre test and post test design. The population in this study amounted to 35 respondents. The technique used for data collection is accidental sampling. Results: Based on the statistical test that the p-value <0.05, it can be stated that HO is rejected, meaning that there is an influence between Kangaroo Method Treatment on Physiological Stress in Low Birth Weight Infants at Rs Annisa Tangerang 2020. There is an influence between Kangaroo  Treatment  Methods  on  Stress Physiology of Low Birth Weight Babies at Rs Annisa Tangerang 2020.